2017
DOI: 10.1177/1077546317740488
|View full text |Cite
|
Sign up to set email alerts
|

The performance of delay compensation in real-time dynamic substructuring

Abstract: Real-time dynamic substructuring (RTDS) is a state-of-the-art experimental technique for evaluating the dynamic performance of a structural system subjected to time-varying loads in civil engineering. The accuracy and stability of RTDS is affected by the natural dynamics of the constituent transfer system. Of various control strategies, and due to the merits of simple implementation and low computational cost, delay-compensation methods have become most pervasive. In this paper, the performance of delay compen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Even when the excitation frequency is above 10 Hz, the errors between the desired and achieved response are still acceptable. The measured results in Figures 15 and 6 illustrate that FSCS brings a successful shaking table RTDHT for the experiment with high frequency component, which cannot be achieved by the conventional delay compensation methods as revealed by Tang et al 38 using the same shaking table as this work.…”
Section: Performance Validation Using a Smale-scale Testingmentioning
confidence: 66%
See 2 more Smart Citations
“…Even when the excitation frequency is above 10 Hz, the errors between the desired and achieved response are still acceptable. The measured results in Figures 15 and 6 illustrate that FSCS brings a successful shaking table RTDHT for the experiment with high frequency component, which cannot be achieved by the conventional delay compensation methods as revealed by Tang et al 38 using the same shaking table as this work.…”
Section: Performance Validation Using a Smale-scale Testingmentioning
confidence: 66%
“…The control scheme of delay compensation [34][35][36][37] is commonly used to compensate the transfer system dynamics in actuator-based RTDHT because of its simple implementation and low computational cost. As Tang et al 38 reported, delay compensation works only when its underlying assumptions that the magnitude error is near to zero and the phase lag is proportional to the frequency of excitation are met. It can be satisfied in actuator RTDHT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al 6 review some of the state-of-the-art delay compensation schemes used in RtHT. For most schemes, the author concludes that improvements in performance were mostly seen within a narrow frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of its limitations is that it can only correct for delays which are integer multiples of the timestep. More forward predictive schemes have been developed by several authors over the years such as those seen in the work of Darby et al 2 and Ahmadizadeh et al 3 Tang et al 4 present a review of such techniques and conclude that performance gains are mostly seen within a narrow frequency band as amplitude ratio and phase errors are seen at high frequencies.…”
Section: Introductionmentioning
confidence: 99%